2017
DOI: 10.1136/bmjopen-2017-017632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a school-based stroke education program on stroke-related knowledge and behaviour modification―school class based intervention study for elementary school students and parental guardians in a Japanese rural area

Abstract: ObjectivesThis study aimed to determine the effect of a stroke education programme on elementary school students and their parental guardians in a rural area in Japan that has high stroke mortality.DesignSchool class based intervention study.SettingEleven public elementary schools in Tochigi Prefecture, Japan.Participants268 students aged 11–12 years and 267 parental guardians.InterventionsStudents received lessons about stroke featuring animated cartoons and were instructed to communicate their knowledge abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…In addition to the need to increase knowledge regarding CPR, it is also important to spread knowledge regarding stroke. In Japan, surveys evaluating the knowledge of stroke have been actively undertaken . Upper elementary or junior high school students are educated, and the students then teach the material to their parents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the need to increase knowledge regarding CPR, it is also important to spread knowledge regarding stroke. In Japan, surveys evaluating the knowledge of stroke have been actively undertaken . Upper elementary or junior high school students are educated, and the students then teach the material to their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Study using school-age youth aged 11-12 years old reported changes in parents' behavior to prevent stroke using stroke education program (Kato et al, 2017). The intervention was carried out on 268 students aged 11-12 years old and 267 parents in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…There are some previous educational studies of enhancing prehospital stroke recognition. The attendees varied from EMTs to laypersons 26–28. Most of the studies showed that the educational programs successfully improved stroke knowledge and awareness.…”
Section: Discussionmentioning
confidence: 99%